Holonic and multi-agent systems for manufacturing 5th international conference on industrial applications of holonic and multi-agent systems, HoloMAS 2011, Toulouse, France, August 29-31, 2011, proceedings - Marík, Vladimír; Vrba, Pavel; Leitão, Paulo (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 5th International Conference on Industrial Applications of Holonic and Multi-Agent Systems, HoloMAS 2011, held in Toulouse, France, August 29-31, 2011. The 25 revised full papers presented were carefully reviewed and selected from 36 submissions. The papers are organized in topical sections on industrial agents, simulation and modelling, planning and scheduling, smart technical systems, and MAS for unmanned aerial vehicles.